Characterizing the genetic diversity of the monkey malaria parasite Plasmodium cynomolgi - Sutton, Patrick L.; Zunping, Luo; Paul C.S., Divis; Friedrich, Volney K.; Conway, D.J; Balbir, Singh; Barnwell, John W.; Carltona, Jane M.; Sullivan, Steven A. (Elsevier B.V., 2016)
Plasmodium cynomolgi is a malaria parasite that typically infects Asian macaque monkeys, and humans on rare occasions. P. cynomolgi serves as a model system for the human malaria parasite Plasmodium vivax, with which it shares such important biological characteristics as formation of a dormant liver stage and a preference to invade reticulocytes. While genomes of three P. cynomolgi strains have been sequenced, genetic diversity of P. cynomolgi has not been widely investigated. To address this we developed the first panel of P. cynomolgi microsatellite markers to genotype eleven P. cynomolgi laboratory strains and 18 field isolates fromSarawak,Malaysian Borneo. We found diverse genotypes among most of the laboratory strains, though two nominally different strains were found to be genetically identical. We also investigated sequence polymorphism in two erythrocyte invasion gene families, the reticulocyte binding protein and Duffy binding protein genes, in these strains. Wealso observed copy number variation in rbp genes.